Análise termodinâmica da reforma autotérmica do metano para a produção de hidrogênio e gás de síntese via maximização da entropia - Souza, Thiago Leandro de (2012)
There are many studies in the literature that propose to conduct a thermodynamic analysis of autothermal reforming reactions. Most of them uses the Gibbs free energy minimization. This methodology doesn't meet directly the thermoneutral condition, limiting operational conditions evaluated in these analyzes. In this work, it were performed a thermodynamic analysis of autothermal reforming of methane using the maximization of entropy, which is most appropriate, because it considers the thermoneutral condition and allows the evaluation of the final temperature of the process. The solution of the non-linear programming problem, generated from the thermodynamic model obtained, was conducted through CONPT2 solver, based on the Generalized Reduced Gradient algorithm (GRG), present in the software GAMS 21.6. It were investigated the effects of pressure, initial temperature, and fed reactants ratios on several evaluated parameters. It were also obtained the optimum operating parameters to obtaining the maximum hydrogen at 1 bar pressure. The maximum amount of hydrogen obtained was 3.24 mol of hydrogen / mol of methane (1000ºC, S/CH4=5 e O2/CH4_0.18). It was evaluated the most favorable conditions to obtaining useful syngas in various types of syntheses. A comparison between the experimental results obtained in the literature showed good agreement with the equivalent simulated data by the used methodology.